Implementing the Team Games Tournament Model to Improve Cognitive Learning Outcomes in IPAS for Fifth-Grade Students - Aziza, Raudhatul; Nashrullah, Nashrullah; Sani, Nurul Kami; Firmansyah, Arif; Khairunnisa, Khairunnisa (FKIP - Universitas Riau, 2025)
This study investigates the effectiveness of the Team Games Tournament (TGT) cooperative learning model in enhancing cognitive learning outcomes among fifth-grade students at SD Inpres Kayuboko in the IPAS subject. The research was driven by low academic performance, largely due to conventional and uninspired teaching practices. Utilizing a Classroom Action Research (CAR) design, the study was conducted over two cycles, each comprising planning, action, observation, and reflection stages. Twenty students participated as research subjects. Data were gathered through cognitive achievement tests, classroom observations, interviews, and documentation. Results from the first cycle showed a learning mastery rate of 70% with an average score of 70.4. In the second cycle, mastery improved to 85% with an average of 78.65. These findings confirm that the TGT model effectively boosts student motivation, participation, and cognitive achievement in a structured and engaging learning environment. The study recommends integrating TGT into classroom instruction to support better learning outcomes and improve overall educational quality in primary schools.